THE MANAGER MULTIPLIER: EQUIPPING YOUR LEADERS TO DRIVE TEAM PERFORMANCE - Annisa Kurnianingsih; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
In today's competitive landscape, organizational performance is fundamentally linked to team efficacy, which is predominantly governed by frontline and middle managers. Despite their pivotal role, these